The N-terminus of the Clostridioides difficile transferase A component directs toxin activity and potency - Robin M. Mullard; Michael J. Sheedlo (mBio)
ABSTRACT Clostridioides difficile infection is the leading cause of antibiotic-associated, hospital-acquired diarrhea in the USA; the pathology of which is mediated by toxins. The presence of a toxin known as the C. difficile Transferase (CDT) in some clinical isolates is linked to severe symptoms including increased incidence of reinfection and higher rates of mortality. Despite its apparent importance to C. difficile pathology, a mechanistic model of how CDT intoxicates cells remains incomplete. Here, we describe a motif composed of acidic and basic residues (the KDKEK motif) that is essential for toxin function. Using Cryogenic Electron Microscopy (Cryo-EM), we highlight an orientation of the KDKEK motif wherein the acidic residues engage structures thought to play an important role during toxin delivery. We thus present a model wherein these interactions prime CDT for entry into host cells. We expect that this model can be extrapolated to other bacterial toxins to understand how they enter cells.IMPORTANCEClostridioides difficile is the leading cause of hospital-acquired infectious diarrhea in the USA. The pathology that accompanies infection is triggered by toxins produced by the bacterium. One of these, the C. difficile Transferase (CDT), has been associated with poorer patient outcomes, although a direct connection to CDT activity has remained elusive. Herein, we present new insight into the mechanism of CDT intoxication and define two regions of the toxin as important for its activity. Moreover, we have generated mutants of CDT that retain the ability to assemble but can no longer intoxicate host cells. In the future, we expect these mutants will serve as valuable tools to help elucidate the role of CDT during infection.